Treatment outcome in patients with HCV Genotype-3a Infection, Treated with 24-Weeks Dual Therapy (Sofosbuvir and Ribavirin) (Medical Forum Monthly, 2024)
Objective: This study was mainly conducted to evaluate the efficacy of sofosbuvir and ribavirin in HCV genotype-3a infection, which is the most common genotype, infecting Pakistani community.Study Design: Open labeled, single center, longitudinal study.Place and Duration of Study: This study was conducted at the Institute of Basic Medical sciences (IBMS), Khyber Medical University, Peshawar from June 2016 to November 2016.Materials and Methods: Total of 80 patients with HCV genotype-3a infection were enrolled. Patients were assigned into four groups including group-A as treatment naïve non-cirrhotic, group-B who were treatment naïve but cirrhotic, group-C as non-cirrhotic cases who were non-responder to peg-interferon and ribavirin and group-D as non-responder cirrhotic cases. Sofosbuvir plus ribavirin was given for 24-weeks. The primary end point was end of treatment (EOT-24) response with 24-weeks therapy, which is defined as HCV RNA level<40IU/ml after 24-weeks of therapy.Results: Among 80 patients, male-female ratio was 56.25%(n=45) and 43.75%(n=35) respectively. Each group has 20 cases. Rate of EOT-24 was 90% (n=18/20) in group-A, 80%(n=16/20) in group-B, 85%(=17/20) in group-C and 75%(n=15/20) in group-D. The EOT-24 was 85%(n=34/40) in all treatment Naïve cases, while 77.5%(n=31/40) was observed in all non-responder cases. The overall response was 82.5%(n=66/80).Conclusion: Results of this study confirm strong efficacy of dual therapy in both treatment naïve and previously non-responder cases, which may be either cirrhotic or non-cirrhotic, with chronic hepatitis-C genotype-3a infections.